Relationship between Corporate Social Responsibility and Earning Quality of Hotels Business in Songkhla Province - ศิริพงษ์, วีระวรรณ; คล้ายแก้ว, ณัฏฐณิชา; แซ่เจีย, ตติยา; ไชยถาวร, ปิยรัตน์; บุตรจริยะ, สุดารัตน์; สุทธิพันธุ์, มัทนชัย (JOURNAL OF SOUTHERN TECHNOLOGY, 2019)
Objectives of this study are (1) to investigate the level of corporate social responsibility hotel business in Songkhla Province, and (2) to test the relationship between corporate social responsibility and earning quality of hotel in Songkhla Province. 100 hotels in Songkhla Province are used to be the sample. Mail questionnaire is used to collect the data. Descriptive analysis and multiple regressions are used to analyze the data. As the results, the most common of corporate social responsibility is in customer topic the highest level, while the other topics of corporate social responsibility are in the high level. Moreover, there is a positive significant relationship between customer, environment, business ethics, and earning quality.